Analysis of Mathematical Problem Solving Ability on Circle Material Class V Madrasah Ibtidiyah - Khadijah, Siti; Siregar, Nurdiana (Universitas Negeri Makassar, 2025)
(The background in this study is the ability to solve the problem msalah students in mis Nurul Yaqin still classified as sufficient, students are not able to understand mathematical concepts. In solving the problem students still forget the steps of solving it. (2) The purpose of this study is to analyze the problem-solving ability of Class V students (3) The research method used is qualitative analysis by sampling using purposive sampling technique. Data collection techniques used triangulation techniques that are matched with observations, interviews and documentation of student test results. (4)The results of the study were seen based on the results of students ' answers that high Category problem-solving skills are able to solve problems well followed through the settlement steps of understanding the problem, drawing up a settlement plan, solving the problem, and re-examine. Then the ability to solve problems in the medium category is still in sufficient condition, less in understanding the problem but can solve the problem, they are only guided by the formula alone. While the ability to solve the problem of low category is still in poor condition, from all steps of problem solving need more teacher guidance. (5) The results of this study, teachers should play a role in guiding students, teachers should instill in students the process of problem solving properly and correctly. Teachers should Group students according to student abilities, student learning needs or the learning style of each student to make it easier to guide according to their respective abilities.